Directionality of coupling from bivariate time series: how to avoid false causalities and missed connections - Palus, Milan; Vejmelka, Martin (Physical review. E, Statistical, nonlinear, and soft matter physics, 2007)
We discuss some problems encountered in inference of directionality of coupling, or, in the case of two interacting systems, in inference of causality from bivariate time series. We identify factors and influences that can lead to either decreased test sensitivity or false detections and propose ways to cope with them in order to perform tests with high sensitivity and a low rate of false positive results.